Household Management Systems and Women's Decision Making Within the Family in Europe. Issue 4 (2nd October 2019) - Mazzotta, Fernanda; Papaccio, Anna; Parisi, Lavinia
ABSTRACT: This paper analyzes household management systems and their effect on intrahousehold gender differences in decision making in thirty European countries. The study considers five domains that reflect two types of decisions – time-consuming and frequent decisions like everyday shopping versus infrequent but important decisions like borrowing money or purchasing consumer durables. In time-consuming activities, the gender gap favors women in each system; for infrequent decisions, the gender gap is dependent on the way money is managed and the biggest gap is found in systems where resources are not pooled. This paper also investigates the role of distribution factors in shaping decision-making behavior. For time-consuming decisions, the higher the income (and education) of the woman compared to the man, the less likely she is to make the decisions. For infrequent activities, the higher the income of the woman compared to the man, the more likely she is to make the decisions.